Hubungan Orang Tua Perokok dengan Perilaku Merokok Pada Siswa di SMA Swasta Tangerang Selatan - Annisaa Umara; Indah Oktaviani; Nuraini Nuraini (Nursing Care Journal, 2025)
Parents are the main and first educators for children. Adolescents enter a phase of searching for identity and a period of transition to adulthood. Smoking is a deviant behavior and poses a health risk to teenagers. As many as 8 students at South Tangerang Private High School are used to smoking. The aim of the research was to determine the relationship between smoking parents and smoking behavior among students at South Tangerang Private High School. Cross sectional research design. The sample in the research consisted of 80 students at private high schools. Data analysis used the Chi-Square test. The research results showed that the majority of respondents were 18 years old, their parents were smokers, and students were used to smoking. There is a relationship between smoking parents and students' smoking behavior (P value= 0.013; α<0.05). It is hoped that this research can be used as material for school evaluations regarding student smoking behavior.